2013
DOI: 10.1007/s10964-013-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Closeness in Mexican-Origin Adolescents’ Relationships with Mothers, Fathers, and Same-Sex Friends

Abstract: Research on the associations between parent-adolescent relationships and friendships among Latinos is limited. Drawing on developmental and ecological perspectives, we examined bidirectional associations between parental warmth and friendship intimacy with same-sex peers from early to late adolescence using a longitudinal cross-lag panel design. Parent-adolescent immigration status and adolescent gender were examined as moderators of these associations. Home interviews were conducted with 246 Mexican American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…Among Vietnamese Australians (Rosenthal, Ranieri, & Klimidis, 1996) and Chinese university students in Canada (Tang & Dion, 1999), boys tend to be more similar than girls to their parents in terms of normative collectivism and traditionalism. Among Mexican American adolescents in the United States, perceptions of warmth from both mothers and fathers in early adolescence are related to later intimacy in friendships in girls, whereas only warmth from fathers is related in boys (Rodríguez, Perez-Brena, Updegraff, & Umaña-Taylor, 2014). Cultural messages may be delivered differently or interpreted differently based on gender.…”
Section: Specificity Principle: Peoplementioning
confidence: 99%
“…Among Vietnamese Australians (Rosenthal, Ranieri, & Klimidis, 1996) and Chinese university students in Canada (Tang & Dion, 1999), boys tend to be more similar than girls to their parents in terms of normative collectivism and traditionalism. Among Mexican American adolescents in the United States, perceptions of warmth from both mothers and fathers in early adolescence are related to later intimacy in friendships in girls, whereas only warmth from fathers is related in boys (Rodríguez, Perez-Brena, Updegraff, & Umaña-Taylor, 2014). Cultural messages may be delivered differently or interpreted differently based on gender.…”
Section: Specificity Principle: Peoplementioning
confidence: 99%
“…Some associations, however, might Mother-Adolescent Agreement 20 be more pronounced for fathers, because their involvement with their children is less scripted than mothers' (Crouter et al 1999). These assumptions remain to be tested, however, because paternal warmth was found to decrease over time, whereas maternal warmth remained stable (Rodríguez et al 2013). Another possible avenue of research would be to test whether parent-adolescent agreement is higher in same-sex parent-child dyads than in opposite-sex dyads because of similar gender roles.…”
Section: Limitationsmentioning
confidence: 95%
“…Furthermore, in a recent study, adolescents reported on maternal and paternal warmth over a 5-year period (Rodríguez et al 2013). The results indicated that paternal warmth was reported to decrease, whereas maternal warmth remained stable over time.…”
Section: Mother-adolescent Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…1994). Adolescents who get emotional support from their friends showed higher self-confidence, emotional regulation ability and more positive social abilities (Rodrı´guez, Perez-Brena, Updegraff, & Uman˜a-Taylor, 2014).…”
Section: Introductionmentioning
confidence: 99%